2006
DOI: 10.1007/11941354_26
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Human-Robot Interaction Through Telepresence Board Games

Abstract: This paper presents an experimental test bed for exploring and evaluating human-robot interaction (HRI). Our system is designed around the concept of playing board games involving collaboration between humans and robots in a shared physical environment. Unlike the classic human-versusmachine situation often established in computer-based board games, our test bed takes advantage of the rich interaction opportunities that arise when humans and robots play collaboratively as a team. To facilitate interaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…On the other hand, the human collaborator was perceived as more credible and socially present, but it had no effect on the actual performance on the task as there was no significant difference in participant's performance between the collaborator conditions. Current results support the notion that understanding emotional and social cues underlying such collaboration from the human perspective, it would be possible to design more helpful and intelligent robots which act according to behavioral patterns that humans can understand and relate to [31]. Especially if we consider humans who will have a longer and more meaningful interaction with robot collaborators, as this study found that those individuals reported higher scores on all of the perceived social categories, except on the Reliability.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…On the other hand, the human collaborator was perceived as more credible and socially present, but it had no effect on the actual performance on the task as there was no significant difference in participant's performance between the collaborator conditions. Current results support the notion that understanding emotional and social cues underlying such collaboration from the human perspective, it would be possible to design more helpful and intelligent robots which act according to behavioral patterns that humans can understand and relate to [31]. Especially if we consider humans who will have a longer and more meaningful interaction with robot collaborators, as this study found that those individuals reported higher scores on all of the perceived social categories, except on the Reliability.…”
Section: Resultssupporting
confidence: 77%
“…The "Sheep and Wolves" is a classic board game, where humans and robots collaborate as independent members of the wolf team. They hunt a single sheep in an attempt to surround it [27,31]. In the "Tic-tac-toe" game the robot and a human can move game pieces on a physical board and collaborate as equals [41].…”
Section: Serious Gamesmentioning
confidence: 99%
See 1 more Smart Citation
“…1. ) is our attempt to evaluate human-robot interaction through the use of games (Xin & Sharlin, 2006). We are particularly interested in the social aspects of collaboration between humans and robots such as teamwork and group dynamics.…”
Section: Sheep and Wolvesmentioning
confidence: 99%
“…We asked participants to play one game in each condition and assessed the gameplay experience with post-test questionnaires. We performed the pilot study with 5 participants and the actual study with 14 participants (Xin & Sharlin, 2006). One of the interesting results found in the pilot study was that human players trusted the assertive robots more than the submissive robots when it comes to decision making.…”
Section: Sheep and Wolvesmentioning
confidence: 99%